INOVASI NUGGET AYAM MENGGUNAKAN UBI JALAR UNGU DI DESA REUDEUP, MONTASIK KABUPATEN ACEH BESAR - Ika Rezvani Aprita; Chairil Anwar; Mulla Kemalawaty (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
This community service activity intended to socialize to the communities by improving knowledge and skills through the utilization of the potential of purple sweet potato in the processing of chicken meat nuggets in Reudeup Village, Montasik District, Aceh Besar Regency. The community service group team consisting of several lecturers assisted by students conducted a survey and situation analysis of the village so that problems could be identified. Based on the survey, the problems faced by the community were: the low level of public knowledge about the use of purple sweet potato as a commodity that can be used in the processing of chicken meat nuggets, lack of alternatives and innovations in food products that use local processed containing anthocyanins, chicken farmers tend to sell chickens without further processing into processed products. The solution of the problems encountered by the community are through efforts to realize diverse food consumption patterns, nutritionally balanced, safe and halal, as well as sufficient composition to meet nutritional needs to support a healthy, active, and productive lifestyle through innovation in the use of purple sweet potato and livestock (chicken) by processing them into chicken meat nuggets. The result of this community service was that people understand and know the processing of chicken meat into chicken nuggets by utilizing the purple sweet potato innovation from their plantation products and able to practice it so that it can improve the level of the economy in daily needs